2021
DOI: 10.1111/cdev.13554
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Goals Influence Their Responses to Children’s Performance: An Experimental Study in the United States and Hong Kong

Abstract: This research examined the role of mothers' self-worth and self-improvement goals in their responses to children's performance in the United States (80% European American) and Hong Kong (100% Chinese). Mothers (N = 330) were induced to prioritize self-worth or self-improvement among children (M age = 10.24 years; 48% girls) . Mothers induced to prioritize self-worth (vs. self-improvement) used more success-oriented responses in both regions (ds = 0.53 and 0.35). Mothers induced to prioritize self-improvement (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The study found that failure-oriented responses may hurt children's self-worth and inhibit their emotional function [12]. Additionally, some experimental and longitudinal studies have found that parents' response to children's performance predicts children's self-esteem [6,9,10]. Therefore, we hypothesize that parents' success-oriented response might positively predict children's self-esteem, while parents' failure-oriented response might negatively predict children's self-esteem.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The study found that failure-oriented responses may hurt children's self-worth and inhibit their emotional function [12]. Additionally, some experimental and longitudinal studies have found that parents' response to children's performance predicts children's self-esteem [6,9,10]. Therefore, we hypothesize that parents' success-oriented response might positively predict children's self-esteem, while parents' failure-oriented response might negatively predict children's self-esteem.…”
Section: Introductionmentioning
confidence: 88%
“…According to social-cognitive developmental perspective theory, children may infer parents' goals from their responses [8]. When parents use success-oriented responses more frequently, children assume that their parents care about their self-worth [9], which helps them focus on their self-esteem and feel appreciated and loved. According to self-determination theory [6], those feelings may satisfy children's basic need for relatedness and love, promoting children's essential psychological function development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By constantly encouraging children, parents ensure the satisfaction of their children's competence and autonomy needs. Therefore, the children will experience greater pleasure and efficacy while performing their tasks and be happier and prouder of their accomplishments [4,15]. Additionally, this has a good predictive value for the children's eventual subjective well-being [6].…”
Section: Parents' Response and Children's Subjective Well-beingmentioning
confidence: 99%
“…Even today, parents act on these ideas. When reminded of the importance of self-esteem, parents readily dole out more praise (Ng et al, 2021).…”
mentioning
confidence: 99%